Childhood cancer in Ireland: a population-based study. Issue 10 (12th June 2007) - Stack, M; Walsh, P M; Comber, H; Ryan, C A; O'Lorcain, P
Abstract : Background: Population-based studies of childhood cancer incidence, survival and mortality make an important contribution to monitoring the successful implementation of new treatment guidelines and to understanding the epidemiology of these diseases. Methods: We analysed incidence and survival data for cancers diagnosed in children under 15 years of age in the Republic of Ireland during 1994–2000 (the first 7 years of National Cancer Registry coverage), and longer term mortality trends. Results: World age-standardised incidence rates in Ireland averaged 142 cases per million children per year, slightly higher than the European average and slightly lower than the US average, although differences varied by diagnostic group. Observed 5-year survival in Ireland (79% overall) was slightly higher than European and US averages, and was significantly higher for acute non-lymphocytic leukaemia (67%) and (compared with the USA) significantly lower for Hodgkin lymphoma (83%). No significant increases in incidence rates were evident from the available 7 years' data, either overall or for particular diagnostic groups. Rates of childhood cancer mortality have declined markedly since the 1950s. Conclusions: Data presented here are in line with other developed countries and suggest major improvements in treatment and consequent survival.